2020
DOI: 10.3389/fphar.2020.00576
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-I Mimetic Peptide L-4F Suppresses Granulocytic-Myeloid-Derived Suppressor Cells in Mouse Pancreatic Cancer

Abstract: L-4F is an apolipoprotein A-I (ApoA-I) mimetic peptide, it was engineered to imitate the antiinflammatory and anti-oxidative activity of ApoA-I. In this paper, H7 cell was used to construct a mouse model of pancreatic cancer in situ, and the mice were treated with L-4F. Then, the development of pancreatic cancer and myeloid-derived suppressor cells (MDSCs) infiltration were investigated in vivo. After L-4F treatment, the differentiation, proliferation and apoptosis of MDSCs were detected in vitro. Moreover, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…Apolipoprotein A-I mimetic peptide L-4F can inhibit the differentiation and activation of MDSCs by downregulating the signal transducer and activator of transcription (STAT)3 signaling pathway of MDSCs. L-4F has the potential to be used as an adjunctive drug for ICI treatment [ 109 ]. In 2016, Huang et al [ 110 ] found that ltp-1, another inhibitor of the STAT3 signaling pathway, can inhibit the growth of pancreatic cancer in vivo and in vitro.…”
Section: Research Progress On Treatment With Icismentioning
confidence: 99%
“…Apolipoprotein A-I mimetic peptide L-4F can inhibit the differentiation and activation of MDSCs by downregulating the signal transducer and activator of transcription (STAT)3 signaling pathway of MDSCs. L-4F has the potential to be used as an adjunctive drug for ICI treatment [ 109 ]. In 2016, Huang et al [ 110 ] found that ltp-1, another inhibitor of the STAT3 signaling pathway, can inhibit the growth of pancreatic cancer in vivo and in vitro.…”
Section: Research Progress On Treatment With Icismentioning
confidence: 99%
“…vivo studies (24,(30)(31)(32)(33)(34)(35)(36)(37)(38). In the hematologic tumors, there was a relatively low level of HDL/ApoA-I in patients with acute lymphoblastic leukemia at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibits inflammatory conversion of HDL by hydroperoxyoctanedecanoic acid (HODE precursor). 4F has also been found to reduce MDSC levels, downregulate surface TLRs and deplete cholesterol in lipid rafts [117 ▪ ,118,119]. However, L-4F was active in mice with functional immune systems, which may potentially limit the target population [120].…”
Section: Therapiesmentioning
confidence: 99%